Protective effects of Spirulina microalgal extracts on Doxorubicin-induced cardiotoxicity in rats (Indian Journal of Veterinary Pathology, 2025)
The current study was conducted to assess the cardio protective potential of Spirulina microalgal extract (SME) in male Wistar rat model of doxorubicin-induced cardiotoxicity. The study consisted of sixgroups, comprising of six rats in Group I and eight rats in Groups II to VI. Group I rats received PBS orally daily for five weeks, Group II to VI rats received doxorubicin (DOX) @ 3.5 mg/kg bw intraperitoneally twice a week from 3rd to 5th week of the experiment period. In addition to DOX, Group III received vitamin E @ 200 mg/kg and Selenium @ 400 µg/kg bw orally; Group IV, V and VI rats received SME @ 250 mg/kg; 500 mg/kg and 1000 mg/kg bw orally daily for five weeks, respectively. The study revealed a significant negative variation in feed and water intake, body weight, heart weight, hematological, biochemical and pathomorphological parameters of heart in Group II, when compared to Group I. The changes caused by DOX were alleviated in SME treatment groups in a dose dependent manner. Similarly, amelioration of DOX induced cardiotoxicity was also observed in vitamin E and selenium group. Histopathologically, the SME treatment groups showed substantial improvement in toxicity lesions ofthe heart compared to Group II rats. The cardio protective efficacy of SME @ 250 mg/kg was lower than that of vitamin E and selenium, while the 500 mg/kg SME group showed slightly better protection and 1000 mg/kg SME showed highest protection, surpassing the effects of vitamin E and selenium.